2000
DOI: 10.2337/diacare.23.7.951
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a questionnaire to evaluate patient satisfaction with diabetes disease management.

Abstract: OBJECTIVE: To develop a reliable and valid questionnaire to measure patient satisfaction with diabetes disease management programs. RESEARCH DESIGN AND METHODS: Questions related to structure, process, and outcomes were categorized into 14 domains defining the essential elements of diabetes disease management. Health professionals confirmed the content validity. Face validity was established by a patient focus group. The questionnaire was mailed to 711 patients with diabetes who participated in a disease manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…The correct answer for each question carried a score of 20%. The test was validated by a method similar to the one developed by Paddock et al (20).…”
Section: Research Design Andmentioning
confidence: 99%
“…The correct answer for each question carried a score of 20%. The test was validated by a method similar to the one developed by Paddock et al (20).…”
Section: Research Design Andmentioning
confidence: 99%
“…The PSQ remains the only comprehensive patient satisfaction questionnaire that is designed specifically for use in the British general practice context. Other more recent questionnaires are non-UK based and/or designed for hospital patients [15][16][17] and recent British measures are designed to look at specific aspects of the service such as care across the primary/ secondary interface. 18 Initial tests on one sample of patients in Norfolk suggested that the questionnaire was internally reliable and valid.…”
mentioning
confidence: 99%
“…Thus, a wellvalidated diagnostic tool may be helpful to identify specific obstacles against the initiation of insulin treatment. There are some questionnaires that measure different aspects of satisfaction with treatment or diabetes-related burdens or stress (11)(12)(13)(14)(15)(16)(17), but presently, to our knowledge, no specific measurement of the psychological barriers to insulin treatment has been created, validated, and published.…”
mentioning
confidence: 99%